"Grife isso : eu uso marca de luxo!: uma análise do consumo de produtos de griffes por indivíduos de classes populares" - Adriana Pimentel Seixas (2009)
Considering that the luxury market presented a remarkable growing in Brazil, specially on the matter of it´s consume by the popular classes, that each day search for products carring a famous brand, this project had as a primordial goal to enfatize this products and luxury goods (a luxury that bring, in its core, emotions and experiences, possessing meanings and feelings) by people who present a lower purchasing power. A luxury market that before, was only destinated to the wealthiests classes. Lxury products where pleasure and impulsiveness / compensation are present, determinated by factors such as: image quality, hedonism, the concerning with the self appearance and social distinction.